2011
DOI: 10.1128/aem.05093-11
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Manipulation of Aspartate Pathway Genes for l -Lysine Overproduction from Methanol by Bacillus methanolicus

Abstract: We investigated the regulation and roles of six aspartate pathway genes in L-lysine overproduction in Bacillus methanolicus: dapG, encoding aspartokinase I (AKI); lysC, encoding AKII; yclM, encoding AKIII; asd, encoding aspartate semialdehyde dehydrogenase; dapA, encoding dihydrodipicolinate synthase; and lysA, encoding meso-diaminopimelate decarboxylase. Analysis of the wild-type strain revealed that in vivo lysC transcription was repressed 5-fold by L-lysine and induced 2-fold by DL-methionine added to the g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
33
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 42 publications
2
33
0
1
Order By: Relevance
“…We previously presented a total of 14 different wild-type isolates of B. methanolicus (10), and among these, MGA3 has been the major model strain used for metabolic engineering (9,11,12,26,27,32). The majority of these strains-including MGA3-have been isolated from soil samples in the Minnesota area, while one strain, PB1, has been isolated from a sugar beet factory wastewater treatment system in Europe (20).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously presented a total of 14 different wild-type isolates of B. methanolicus (10), and among these, MGA3 has been the major model strain used for metabolic engineering (9,11,12,26,27,32). The majority of these strains-including MGA3-have been isolated from soil samples in the Minnesota area, while one strain, PB1, has been isolated from a sugar beet factory wastewater treatment system in Europe (20).…”
Section: Resultsmentioning
confidence: 99%
“…Some B. methanolicus genes en- (27,39), and hom1 and hom2 (encoding homoserine dehydrogenase [HD I and II, respectively]) (9). The asd (encoding aspartate-semialdehyde dehydrogenase) and dapA (encoding dihydrodipicolinate synthase) genes were also cloned by us (27), and we recently demonstrated that they both encode active enzymes (32). Overexpression of dapG, lysC, and yclM increased L-lysine production in wild-type B. methanolicus MGA3 up to 60-fold (corresponding to 11 g liter Ϫ1 ) in fed-batch methanol cultivation (27), and we showed that hom1 is the major target for S-(2-aminoethyl)-Lcysteine (AEC) resistance in B. methanolicus (9).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…mxaFI genes have been found in some Actinobacteria and methylotrophy are widely distributed in this taxon (Anesti et al, 2004;Hung et al, 2011). Biochemically and evolutionary distinct methanol oxidoreductases of Gram positives cannot be detected with currently available primers (for example, those of B. methanolicus; Hektor et al, 2002;Naerdal et al, 2011). Thus, future efforts are needed to improve the assessment of Gram-positive methylotrophs.…”
Section: Diversity Of Soil Methylotrophsmentioning
confidence: 99%
“…We previously showed that overexpression experiments can be used to efficiently analyze the role and regulation of a number of genes in the L-lysine biosynthetic pathway in B. methanolicus (30,38). Here, we used an analogous approach to map the roles of the gltAB, gltA, gltA2, glnA, and yweB genes.…”
Section: Geobacillus Thermodenitrificans (Yp_001125407) Bacillus Licmentioning
confidence: 99%